REMTERNETUG: AN INVESTIGATIONAL MONOCLONAL ANTIBODY AGAINST Β-AMYLOID FOR THE TREATMENT OF ALZHEIMER’S DISEASE (AD) - KAUR, MANMEET; MISRA, SAURAV (International Journal of Current Pharmaceutical Research, 2025)
In today's aging world, Alzheimer’s disease (AD) is a leading cause of dementia and a major chronic illness among the elderly, affecting 55 million people. The World Health Organization (WHO) has identified AD as a top public health priority. Unfortunately, there are currently no definitive cures for this condition. Treatment strategies primarily focus on alleviating symptoms, such as acetylcholinesterase inhibitors (AChEI) and the N-Methyl-D-aspartate (NMDA) antagonist Memantine. The most effective approaches for managing the disease at present appear to involve a combination of medication and non-medication-based therapies aimed at stimulating cognitive reserve. Over the past two decades, several drugs have been discovered that target the established biological indicators of AD, including the build-up of β-amyloid aggregates and the accumulation of hyperphosphorylated tau protein within cells. The amyloid cascade hypothesis is a useful framework for developing therapies for Alzheimer’s disease (AD). Experimental treatments have targeted amyloid b1-42 (Aβ) due to its neurotoxic effects and potential adverse effects on the brain, detectable through positron emission tomography (PET). Recent trials support the clinical efficacy of third-generation anti-amyloid immunotherapies in reducing brain Aβ burden and preventing cognitive decline. This has led to the recent FDA approval of aducanumab and lecanemab under an accelerated approval pathway. In this overview, we aimed to assess the safety and effectiveness of Remternetug in treating AD. Remternetug is an enhanced version of donanemab that also targets N-terminal pyroglutamated Aβ. The initial findings show promise for the development of an effective novel drug. However, more phase III studies are needed to provide sufficient clinical evidence for its effectiveness. Current evidence is limited to phase I and II studies and has yet to prove its worth in a larger population.